el-Cami’ li sıfati eştati’n-nebati ve durûbi envâ’i’l-müfredat = Compendium of the properties of diverse plants and various kinds of simple drugs. - el-İdrisi, Ebu Abdillah Muhammed b. Muhammed b. Abdillah b. İdris. (Frankfurt)
2 c. 3 c.’te.